Queer Dickens erotics, families, masculinities - Furneaux, Holly (Oxford University Press, 2009)
Furneaux offers a new reading of Dickens. She argues that rather than representing a largely conventional view of sexuality and gender his corpus is distinctly queer, displaying a fascination with the diversity of gender roles, the expandability of notions of the family and the multiplicity of sexual desire.